An Empirical Analysis of the Impact of Credit Risk Management on the Financial Performance of Commercial Banks in Nigeria - Oyasor, Emmanuel Imuede (Ilomata International Journal of Tax and Accounting, 2024)
This study investigates the impact of credit risk management on the financial performance of commercial banks in Nigeria. It aims to assess how key credit risk indicators—capital adequacy ratio (CAR), cost-to-income ratio (CIR), and non-performing loans (NPL)—influence bank profitability. The study employs a panel regression model, utilizing secondary financial data from commercial banks operating between 2010 and 2022, sourced from the Central Bank of Nigeria and other official records. Descriptive analysis, normality tests, correlation analysis, and panel regression techniques are applied to examine the relationships between variables. The results reveal a strong negative correlation between CAR and CIR, indicating that higher capital adequacy is associated with improved financial efficiency. However, regression analysis shows no statistically significant relationship between credit risk management variables and financial performance, as reflected in return on equity (ROE) and return on assets (ROA). This suggests that while credit risk management practices affect cost efficiency, their direct impact on profitability remains inconclusive. The findings highlight the complexity of credit risk management in commercial banking. While maintaining adequate capital buffers contributes to cost efficiency, other external economic factors may be more significant in determining overall profitability. The study underscores the need for commercial banks to refine their risk assessment and mitigation strategies to enhance financial stability and performance. Despite credit risk management's theoretical significance, its direct influence on financial performance appears limited. To optimize financial outcomes, banks should implement more effective risk assessment frameworks and recovery mechanisms for non-performing loans. This study contributes to the limited empirical research on credit risk management in Nigeria by providing a comprehensive panel data analysis. Unlike previous studies, it examines both correlations and regression effects, revealing that credit risk management practices more influence cost efficiency than profitability.